The SER spread under the ECB quantitative easing - Jakub Jakl (European Financial and Accounting Journal, 2019)
This paper discusses the effects of the ECB's asset purchase programmes (APPs) on the SER spread, while the main focus is given to detail intraday analysis of implementation of the Public Sector Purchase Programme (PSPP). The SER spread is perceived as an important indicator of interbank trust in the Eurozone and its elevated level normally signals distortion and mistrust among commercial banks with a power to spill over into the whole financial sector. Recent development on interbank markets and especially within monetary policy in the Eurozone could have impaired the ability of the SER spread to act as a proxy for global systemic risk. The SER spread in this study was constructed and calculated using relevant European financial data and the consequent analysis was made on intraday and high-frequency (HF) 2015-2017 data. The ECB's APP, mainly PSPP, together with other instruments of monetary policy have impact on both legs of the SER spread and this paper tries to identify and quantify the degree of this effect by detailed HF market data analysis. HF intraday approach analysis is also being implemented in order to identify which leg of the SER spread was decisive in determining the SER spread change in the first three years of the PSPP implementation. Whether it was the "sovereign bond-based leg" directly affected by the ECB's PSPP purchases or the "interbank lending / STIR-based leg".
Keywords: E43; E52; E58; G21; 650; TED Spread; SER Spread; Quantitative Easing; ECB; PSPP